Diversity in the labour market: The legal framework and support services for migrant workers in Germany - Kay Hailbronner (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2007)
This paper describes the legal and regulatory framework under the Immigration Act of 30 July 2004 (Zuwanderungsgesetz). The Immigration Act, made up of several acts and amendments to existing legislation, has established a new concept of managed migration by the Act on Residence, Economic Activity, and Integration of Foreigners on the Federal Territory (Residence Act). This Act describes as its purpose to manage and restrict the influx of foreigners into the Federal Republic of Germany and to enable and organize immigration with due regard to the integration capacity and the interests of the Federal Republic of Germany in terms of its economy and labour market policy.
Keywords: 330